O ensino do Atletismo em ambiente escolar: limitações, abordagens e possiveis adaptações materiais - Matozo Milan, Lucas (2021)
Even with an academic production focused on its application within the school, studies show that athletics is still underutilized. In this sense, the present study aimed to analyze articles related to teaching and the possible adaptations of materials in school athletics, as well as the problems and applications of this content. For this, a narrative review was carried out from 25 sources. With the reading of the sources, the themes were divided into 3 central categories: Limitations and Problems in Teaching, Possibilities in the Teaching of Athletics and Possible Material Adaptations. Finally, it was concluded that there are questions from the authors about the limitations present in schools, as well as trying to understand and analyze why the limitations are present in the school environment, however it was observed that the teaching of athletics in schools can be carried out from different approaches, in addition to the fact that it is possible to make physical and material adaptations to work with athletics tests in the context of school Physical Education.